The Effects of Gait Speed and Psychomotor Speed on Risk for Depression and Anxiety in Older Adults with Medical Comorbidities. Issue 5 (2nd January 2021) - Stahl, Sarah T.; Altmann, Helene M.; Dew, Mary Amanda; Albert, Steven M.; Butters, Meryl; Gildengers, Ariel; Reynolds, Charles F.; Karp, Jordan F.
Abstract : Background/Objectives: Gait speed and psychomotor speed slow with age and may predict neuropsychiatric disease such as depression and anxiety. We explored the relative predictive values of gait speed, psychomotor slowing, and a composite index of these two measures on time to new episode depression or anxiety in older adults at risk for these common psychiatric conditions. Design: Randomized controlled prevention trial with 15‐month follow‐up. Setting: University‐based late‐life mental health research clinic. Participants: Two hundred thirteen individuals, age 60+ years, with subsyndromal symptoms of depression or anxiety and one of the following risk factors for these common conditions: mild cognitive impairment, knee osteoarthritis, or disabilities requiring home‐based care. Intervention: Participants in each of the risk factor groups were randomized to a depression‐specific preventive intervention or usual care. Measurements: Gait speed: 4‐m walk test from the Short Physical Performance Battery. Psychomotor speed: Coding task of the Repeatable Battery for the Assessment of Neuropsychological Status. We created a composite index of slowing by determining whether participants exceeded established cut‐offs for slow performance in both gait speed (≤0.8 m/s) and psychomotor speed (<7 on the coding task). Time to new onset syndromal depression/anxiety was measured using research diagnostic criteria. Results: Fifty‐four participants developed syndromal depression/anxiety (19.5%) over the course of 15 months. Participants with slowing in both areas were over twice as likely to experience new onset depression/anxiety (hazard ratio (HR) = 2.11; 95% confidence interval (CI) = 1.02–4.40, P = .046) compared to participants with no slowing in either area. Slowed gait (HR = 1.88; 95% CI = 0.992–3.55; P = .052) or slowed psychomotor speed (HR = 0.60; 95% CI = 0.14–2.58; P = .488) alone did not increase risk for depression/anxiety. Conclusion: Evaluating both gait and psychomotor speed in older adults with medical comorbidities and sub‐syndromal depression may predict incident mental illness and inform prevention planning. Future research is needed to validate our observations and explore shared neurobiological mechanisms that explain this elevated risk.